A non-randomized study investigating the effectiveness of cognitive reframing in socially disconnected widows - Moses, Victor (The European Research Journal, 2021)
Objectives: Socially disconnected widows usually live a lonely and depressing life with anxiety and low self-worth. Many have contemplated suicide and others have become a victim of suicide already. Evolving an intervention to provide succor to them to take control of their lives may help a great deal. This paper presents the results of a nonrandomized study assessing the potency of cognitive reframing (CR) in reducing social disconnectedness (SD) among the widows.Methods: The pre- and post-data was collected from a non-randomized sample of 41 widows in the treatment group and 45 in the waitlist control group. The mean age of the participants was 41.383 ± 6.730 [95% CI = 39.940–42.940] (min. = 25 - max. = 56) years. The cognitive reframing administered spanned for eight weeks.Results: Analysis of the data collected suggests that cognitive reframing is significantly effective in reducing socially disconnected behavior among the widows in the study. The social disconnected behavior among the widows reduced by 40.95% compared to 8.29% observed in the waitlist control group.Conclusions: The CR technique may be helpful in reducing social disconnectedness in widows. However, further study may be required in a randomized sample to enhance generalization.